Renovation technique for the promotion of the loading class of an old steel truss bridge - Narayan; Pathak, Krishna Kant (Journal of Structural Engineering, 2024)
This research article presents an expeditious renovation technique for the promotion of the loading class of the throughtype historic metal truss bridges. To develop this concept for real-time use, an existing bridge functional for more than 50 years was selected for the assessment. The bridge was modeled in the STAAD Pro software for the analysis of the existing state of the bridge and for the incorporation of the strengthening measures in the bridge model. The main feature of this renovation technique was the proper utilization of the open space available in the sections of the main members which overcome the deficiencies of the existing bridge in comparison to the well-designed conventional steelconcrete composite bridges and the double composite bridges. All the members were found to be safe in design and serviceability. The main concerns along with strengthening the structure were to preserve the historic appearance without replacing any member and to provide a handy and cost-effective method for the rehabilitation of such old bridges.